Cheunti ka khauf: qurani waqai'at nani munni bachon ke liye - Sanisiyan, Khan; Raiz, Afaandi (Paradise Karachi, 2005)
A collection of simplified Quranic stories tailored for young children. It introduces important events and lessons from the Quran, making them accessible and engaging for early learners. Through vibrant illustrations and easy language, it aims to instill moral values and religious teachings in a way that young minds can understand and appreciate.